2012
DOI: 10.1002/ptr.4913
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Inhibitory Effects of Different Parts and Chemical Constituents of Pomegranate on α‐Amylase and α‐Glucosidase

Abstract: Pomegranate has been documented for the management of diabetes in Unani and Chinese medicine. This study compared the effects of the extracts of different pomegranate parts, including juice, peels, seeds and flowers, on carbohydrate digestive enzymes (α-amylase and α-glucosidase) in vitro. The methanolic flower extract inhibited α-amylase and α-glucosidase, while the methanolic peel extract inhibited α-glucosidase selectively. The most active flower extract was subjected to water-ethyl acetate partition. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 17 publications
5
60
0
1
Order By: Relevance
“…Recent studies demonstrated that the flower, peel, and seeds of pomegranate exhibit hypoglycaemic activities in several in vitro and in vivo models [45][46][47]. Phenolic compounds also affect digestive enzymes involved in the hydrolysis of dietary carbohydrates.…”
Section: Bioactivity Of the Treated Juicementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that the flower, peel, and seeds of pomegranate exhibit hypoglycaemic activities in several in vitro and in vivo models [45][46][47]. Phenolic compounds also affect digestive enzymes involved in the hydrolysis of dietary carbohydrates.…”
Section: Bioactivity Of the Treated Juicementioning
confidence: 99%
“…Kam et al [45] investigated the inhibitory activity of pomegranate flower, peel, seed and dried juice on α-amylase and α-glucosidase. The methanol flower extract inhibited both enzymes, while the methanol peel extract selectively inhibited the α-glucosidase.…”
Section: Bioactivity Of the Treated Juicementioning
confidence: 99%
“…In recent years, many phytochemicals have been studied for their inhibitory activity against a-amylase, like green coffee extracts (Narita & Inouye, 2011), tea extracts (Fei et al, 2014;Sun et al, 2016), pomegranate extracts (Kam et al, 2013), etc., and the main components that demonstrated the inhibitory activity were shown to be phenolic compounds. Aqueous extracts from fruits or plants are generally a mixture of polyphenols and soluble polysaccharides, in part due to binding interactions between the two components (Chamorro, Viveros, Alvarez, Vega, & Brenes, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand [16] reported that the inhibition of carbohydrate digestive enzymes and their phenolic content may contribute to the anti-hyperglycemic effects of pomegranate flower and peel, and support their claims in diabetes. Studies carried by [17] indicated that the methanolic extract of pomegranate peel has beneficial influences and could be able to inhibit Al-induced oxidative stress and histo-pathological alternations in liver and kidney of female rats, and these effects may be related to anti-apoptotic and antioxidant activities.…”
Section: Introductionmentioning
confidence: 85%